Including ecosystem descriptors in current fishery data collection programmes to advance towards a holistic monitoring: Seabird abundance attending demersal trawlers. (September 2020) - Louzao, Maite; Ruiz, Jon; Oyarzabal, Iñaki; Basterretxea, Mikel; Pedrajas, Arkaitz; Mugerza, Arnaitz; Krug, Iñigo; Cotano, Unai; Mugerza, Estanis; Zarauz, Lucía; Santurtún, Marina
Abstract: To develop an ecosystem-based approach to fisheries management a holistic perspective is necessary that goes beyond target species management to preserve ecosystem functioning and, therefore, secure future food availability. To achieve these objectives, current fishery data collection programmes should widen their objectives to include the collection of ecosystem descriptors to effectively take advantage of funding and human resources in relation to fisheries monitoring already in place. From an ecological perspective, fishing discards are food subsidies unnaturally available that can profoundly impact the life history traits and population dynamics of seabirds, as well as community structure. In 2015, we took advantage of the Data Collection Framework (DCF) programme, monitoring the Basque trawling fleet, to monitor seabird abundance associated with trawlers as an additional task to be performed by the observers. The main objectives were (1) to develop a standard protocol from an interdisciplinary expert committee, (2) to obtain baseline information of seabird association with trawlers to be able to track changes and (3) to understand seabird abundance in relation to discard facilitation processes based on environmental and fishing parameters. Based on the developed standard protocol, more than 21 species of seabirds were recorded in 241 fishing hauls in the Bay of Biscay (ICES areas 8abd). This biogeographic area is an important migratory flyway and wintering area, where maximum number of seabirds attending trawlers were recorded between December and April (2015–2019). Based on Generalised Linear Models, seabird abundance was higher in multiple situations: harsher environmental conditions, less available discards, shallower areas, increased period of discard availability, higher number of trawlers simultaneously operating in the same fishing ground, in addition to the months of February and April. The core discarding ground was located in the outer French shelf between the latitudinal range of 44.5°N and 46°N, especially for otter trawl fishing. Our approach puts into value the seabird counts that the observers of the DCF can perform systematically, collecting relevant information on the effect of trawling on other biodiversity components such as seabirds. This information will be critical to respond to the application of the reform of the Common Fisheries Policy regarding the effect of the Landing Obligation that seeks fishing sustainability. Highlights: Observers of the Data Collection Framework estimated seabird abundance associated to commercial trawling. 21 species of seabirds were recorded in ICES areas 8abd, with maximum numbers between December and April. Seabird abundance was highly influenced by a combination of fishing and environmental factors. Core discarding ground was located in the outer French shelf. The inclusion of new ecosystem descriptors is compatible with routine fishing monitoring.